The application of traditional elements of a leather vest from the Croatia area in a contemporary collection of women's clothing - Šabarić, Irena (Array, 2021)
Due to the richness and variety of costumes, one leather element from the leather coat (kožuh) has been singled out, which has been developed in a new way and applied in a contemporary clothing collection.A lot of attention has been paid to handmade workmanship and quality, so this collection also has high fashion features. In the art part, through sketches, the selected theme or element is elaborated.Models have been developed and places where and in what way leather elements and mirrors will be applied.The collection transforms the costume element into simple, refined garments, creating a contrast between the old and the new, tradition and modernity.It depicts the present, a contemporary collection created on the foundations of a rich past and tradition.The result is presented in the form of a realized fashion collection of women's clothing with leather ethno applications.